LOX family and ZFPM2 as novel diagnostic biomarkers for malignant pleural mesothelioma - Kim, Min-Kyu (Biomark Res, 2020)
BACKGROUND: Malignant pleural mesothelioma (MPM) is a rare and aggressive cancer that develops in the pleural and outer layer of tissues surrounding the lungs. MPM is primarily caused by occupational exposure to asbestos and results in a poor prognosis. Effective therapeutics as well as early diagnostics for the MPM are still lacking. To identify potential diagnostic biomarkers for MPM, we performed bioinformatics analysis of public database. METHODS: Utilizing databases from Cancer Cell Line Encyclopedia (CCLE) and Gene Expression Omnibus (GEO), we identified several potential candidates that could act as MPM biomarkers. We carried out additional molecular analyses of these potential markers using MPM patient tissue samples via quantitative polymerase chain reaction. RESULTS: We identified Lysyl oxidase (LOX), Lysyl oxidase homologs 1&2 (LOXL1& LOXL2) Zinc Finger Protein, FOG Family Member 2 (ZFPM2) as potential diagnostic biomarkers for MPM. In this study, we found that the LOX family and ZFPM2 showed comparable diagnostic ability to Fibulin-3 or mesothelin (MSLN) and would be better potential biomarkers than Sulfatase 1 (SULF1), Thrombospondin 2 (THBS2) and Cadherin 11 (CDH11). CONCLUSIONS: LOX family and ZPFM2 were identified as novel MPM diagnostic biomarkers which could strengthen MPM clinical diagnostic capabilities.